2016
DOI: 10.1590/1806-9282.62.04.307
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the symptoms and treatment prescribed to hospitalized patients

Abstract: Objective: Evaluation of the presence of symptoms and suitability in the treatment of patients admitted to medical wards at HU-UFSC. Identification of patients eligible for palliative care (PC). Method: A prospective cohort study, which evaluated patients in the first 48 hours of hospitalization (D1) and after 48 hours (D2). On D1, palliative performance and symptom assessment scales were applied (PPS/ESAS). The treatment established for the control of detected symptoms was also identified. On D2, the ESAS sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…The prescriptions for pain control were predominantly "if necessary", prevailing the use of non-opioid analgesics and weak opioids. In the same study, anxiety was not treated in over 75% of the patients 16 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The prescriptions for pain control were predominantly "if necessary", prevailing the use of non-opioid analgesics and weak opioids. In the same study, anxiety was not treated in over 75% of the patients 16 .…”
Section: Discussionmentioning
confidence: 87%
“…The multicentre study Support 15 , conducted in 1995 with 10,000 patients with terminal disease, showed that half of them died with moderate or severe pain, without any analgesic prescription. A recent study with hospitalized patients, not on PC, showed patients with various non-medicated symptoms, including pain 16 . On the other hand, studies with chronic patients under PC demonstrate a good control of symptoms and improvement of the quality of life of these patients 17, 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The study by Roldi and Moritz [33] concluded that due importance is not given to palliative care and that there is a need for optimization and dissemination of this topic among health professionals, mainly due to the growth of aging population and the consequent increase in the prevalence of non-communicable chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Para se garantir assistência efetiva em cuidados paliativos, já existem ferramentas que podem ser utilizadas pelos profissionais, a exemplo da Escala de Avaliação Sintomas de Edmonton (ESAS), que avalia e mensura sinais e sintomas de sofrimento e desconforto como: dor, fadiga, náuseas, depressão, ansiedade, sonolência, apetite, desconforto respiratório e mal-estar geral. Esta avaliação deve ser aplicada diariamente, por meio de perguntas simples e direcionadas para os pacientes ou familiares (16) . Porém, após na análise das entrevistas foi observado que esta ferramenta não era usada pela equipe de cuidados paliativos ou, se era, não se explicava sua função aos familiares.…”
Section: Discussionunclassified